Inorganic elements in sugar samples consumed in several countries - Salles, Paula M. B.; Menezes, Maria Ângela de B. C.; Jaćimović, Radojko; Campos, Tarcísio P. R. (Journal of radioanalytical and nuclear chemistry, 2016)
Sugar is considered safe food ingredient, however, it can present inorganic elements as impurities uptake during cultivation and production process. Therefore, this study aimed at identifies the presence of these elements in granulated and brown sugar samples available for consumption in public places in several countries. The neutron activation technique applying the methodology to analyse larger samples, 5 g-sample, established at CDTN/CNEN based on k 0 -method was used to determine the elemental concentrations. Several essential and non-essential elements were determined in a large range of concentrations. The results are discussed comparing to maximum values foreseen in the international and Brazilian legislations.